Energetic proton acceleration by EMIC waves in Io’s footprint tail - Clark, G.; Szalay, J. R.; Sulaiman, A. H.; Saur, J.; Kollmann, P.; Mauk, B. H.; Paranicas, C.; Hue, V.; Greathouse, T.; Allegrini, F.; Glocer, A.; Garcia-Sage, K.; et al. (Frontiers in Astronomy and Space Sciences, 2023)
In this study, we present a survey of energetic proton observations associated with Io’s footprint tail (FPT) and compare their signatures with in situ measurements of the plasma waves and lower-energy electron environments. We find further supporting evidence that proton acceleration in Io’s FPT is likely a consequence of wave–particle interactions via electromagnetic ion cyclotron waves that are generated by precipitating electrons into Jupiter’s ionosphere. This idea was originally proposed by Clark et al. (2020) and Sulaiman et al. (2020) based on NASA’s Juno mission likely transiting Io’s Main Alfvén Wing (MAW) during its twelfth orbit (i.e., PJ12). Additionally, the analysis of > 50 keV protons presented here highlights important observational details about the Io–Jupiter interaction as follows: 1) proton acceleration in Io’s FPT is a persistent feature and the energy flux carried by the protons is highest at smaller Io-Alfvén tail distances; 2) energetic protons exhibit positive correlations with both plasma waves and <100 keV/Q electrons; 3) during a small number of Io FPT crossings, the protons display finer spatial/temporal structure reminiscent of the electron observations reported by Szalay et al. (2018); and 4) the proton pitch angle distributions are characterized by two types: conic distributions in or near Io’s MAW and isotropic elsewhere.